Self-Confidence Perempuan yang Memilih Menjadi Pihak Ketiga dalam Hubungan Asmara - Ira Mutianing Sari; Zuyyin Choiriyyatun Felasuf; Mochamad Widjanarko (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to explore self-confidence among women who choose to become a third party in romantic relationships. Self-confidence is understood as an individual’s belief in their abilities and self-worth, which is reflected in cognitive, affective, and behavioral aspects. This study employed a qualitative approach using in-depth interviews and observation with female informants involved as third parties in romantic relationships. The findings indicate that self-confidence is reflected in positive self-perceptions, a belief in one’s value within the relationship, and the courage to express feelings and make decisions despite social risks. From an affective perspective, the informants experienced feelings of being valued, desired, and having a meaningful role in their partner’s life. Meanwhile, the behavioral aspect was demonstrated through the informants’ consistency in maintaining the relationship and their willingness to face the social consequences associated with being a third party. This study concludes that self-confidence is shaped not only by internal factors but also by interpersonal relationship dynamics and the fulfillment of emotional needs, providing a more comprehensive understanding of the psychological dynamics of women in complex romantic relationships.